2020
DOI: 10.17784/mtprehabjournal.2020.18.783
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the cervical spine, breathing mode and burnout syndrome in university students with temporomandibular disorder

Abstract: A articulação temporomandibular é responsável por realizar as funções do sistema estomatognático. As desordens que acometem a articulação temporomandibular causando alterações no seu funcionamento resultam no que é conhecido como disfunção temporomandibular (DTM). A etiologia da DTM é complexa e multifatorial, sendo considerada um conjunto de problemas clínicos que envolve não só a ATM, mas estruturas circunvizinhas, podendo estar relacionada com a postura e a mobilidade cervical, a respiração e com fatores ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Similarly, Ferreira et al [34] showed reduction in exion-extension movement of the neck (FRT) in all TMD patients, compared with controls. de Andrade Negrão et al [35] reported lower range of neck movements by using FRT in patients with TMDs compared with healthy controls, but this difference did not reach statistical signi cance, which was in line with the present results. The same results were reported by Ameral et al, [36] and they added that TMD patients had lower neck exion and rotation angle.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, Ferreira et al [34] showed reduction in exion-extension movement of the neck (FRT) in all TMD patients, compared with controls. de Andrade Negrão et al [35] reported lower range of neck movements by using FRT in patients with TMDs compared with healthy controls, but this difference did not reach statistical signi cance, which was in line with the present results. The same results were reported by Ameral et al, [36] and they added that TMD patients had lower neck exion and rotation angle.…”
Section: Discussionsupporting
confidence: 88%